Influence of preconception carbohydrate intake on hypertensive disorders of pregnancy: The Japan Environment and Children's Study. Issue 2 (21st November 2022) - Omoto, Takahiro; Kyozuka, Hyo; Murata, Tsuyoshi; Imaizumi, Karin; Yamaguchi, Akiko; Fukuda, Toma; Isogami, Hirotaka; Yasuda, Shun; Sato, Akiko; Ogata, Yuka; Shinoki, Kosei; Hosoya, Mitsuaki; et al.
Abstract: Aim: Hypertensive disorders of pregnancy (HDP) are a crucial cause of morbidity and mortality. We aimed to examine whether preconception carbohydrate intake is associated with new‐onset HDP and small for gestational age (SGA) births. Methods: We identified 93 265 normotensive (primiparous, 37 387; multiparous, 55 878) participants from the Japan Environmental Children's Study database who delivered between 2011 and 2014. After excluding participants with multiple gestations, preconception hypertension, and insufficient data, primiparous and multiparous participants were categorized into five groups according to their preconception carbohydrate‐intake quintiles (Q1 and Q5 were the lowest and highest groups, respectively). Multiple logistic regression analysis was performed to identify the effect of preconception carbohydrate intake on early (<34 weeks) and late‐onset (≥34 weeks) HDP and the incidence of SGA births. Results: With the middle carbohydrate intake group (Q3) as a reference, the risk for late‐onset HDP among multiparous women was higher in the Q5 group (adjusted odds ratio [aOR] 1.31, 95% confidence interval [CI] 1.02–1.69). The incidence of SGA births was higher in the Q1 group among both primiparous (aOR 1.16, 95% CI 1.01–1.33) and multiparous women (aOR 1.16, 95% CI 1.02–1.32). Conclusions: Excessive carbohydrate intake increases the incidence of HDP in multiparous women, while low‐carbohydrate intake increases the incidence of SGA births. New recommendations for preconception carbohydrate intake are required to prevent major HDP‐related complications.